A review on the antibacterial potential of cantabiline-based derivatives - Noora Abdulaziz; Yasser Mustafa (University of Mosul, 2020)
Objective: The target of this review study is to highlight the importance of cantabiline and its derived compound as antibacterial agents. Also, to take into consideration the characteristic structural features that can enhance the capability of these compounds to fight pathogenic bacteria.Methods: The recently available reports concerning the antibacterial activity of cantabiline-derived compounds have been reviewed efficiently. The outcomes of these reports have been also analyzed to detect the proper substituents that can enhance the target activity.Results: The hand-availability of antibacterial agents, as well as their inadvisable utilization, resulted in a mounting health problem named multi-drug resistant bacterial strains. To handle this emerging issue, the design and synthesis of agents with a powerful ability to fight such bacterial strains is becoming a pressing need.Conclusion: This review study has concluded that cantabiline and its derived compounds may represent hopeful antibacterial agents. Also, they can address several mechanisms acquired by bacteria for resisting the currently-available antibacterial agents.